Diaspora politics and a rising China: Ambivalent ties amid geopolitical changes - LIU, Jiaqi M. (Institutional Knowledge at Singapore Management University, 2025)
Over the past decade, the rise of China on the global stage has witnessed the emergence of members of the Chinese diaspora as new meso-level actors in mediating Sino-Western relations. As part of China’s burgeoning “public diplomacy” around the globe, Chinese migrants organize cultural events to establish grassroots and semi-official exchanges between China and the West. This chapter provides a state-of-the-art examination of so-called “diasporic public diplomacy” whereby the Chinese diaspora plays an increasingly important role in promoting China’s soft power abroad. Based on long-term fieldwork in a prominent emigrant community, I analyse how Chinese national policies envision two specific groups within the broader diaspora—namely, diasporic elites and overseas students—as “public diplomats.” My empirical study shows that given China’s global ascendancy, these geopolitics-oriented diaspora policies have profound implications for Chinese migrants’ changing ties with their homeland and host societies. By situating the Chinese diaspora within broader structural changes, this chapter makes theoretical contributions to grounding Sino-European relations in the specific narratives, experiences, and struggles of Chinese migrants as rising geopolitical intermediaries.